The Studying of Declining Reservoir Pressure on Natural Gas Sweetening Process: A Case Study and Simulation (Global Journals of Research in Engineering, 2012)
Natural gas is considered as one of the most popular source of energy in recent era and future as well. However, raw natural gas usually contents several of nonhydrocarbon components for instance, hydrogen sulphide and carbon dioxide. Indeed, these impurities are undesirable compounds and cause many problems for example, corrosion and environment pollution. Moreover, amine gas sweetening process is considered the most popular technology to remove acid gases from natural gas stream. However, when the hydrocarbons reservoir pressure declines, new wells are drilled to maintain production and enhanced oil recovery methods are also applied at the end age of the reservoir. As a result, the declining of the reservoir pressure leads to decline the operation pressure for the amine contactor tower and it may lead to significant effects on gas sweetening process efficiency and performance. Therefore, this study aims to simulate gas-sweetening process for given raw natural gas stream that it contents high quantity of acid gases by using Aspen HYSYS simulator program and then examine the effects of declining reservoir pressure on the sweetening process. The case study gas stream operation pressure is about 7000 Kpa. However, the study found that when the sour gas pressure declined that will effect acid gases loading in amine solution.
Keywords: Natural gas sweetening; reservoir pressure; amine solution; process simulation; Aspen Hysys; process efficiency